Optical laminates and antireflective coatings

By employing an optical laminate structure of cerium oxide and silicon dioxide on a resin substrate, the durability and manufacturability issues of lightweight anti-reflective films are solved, achieving anti-reflective effects in harsh environments, making them suitable for mobile device displays.

CN117980786BActive Publication Date: 2026-11-06DEXERIALS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280064753.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-01
Filing Date
2022-09-28
Publication Date
2026-11-06
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

Existing technologies struggle to form durable, low-refractive-index, and easily manufactured anti-reflective films on lightweight resin substrates, especially in harsh environments such as pen touch modules where peeling and damage are common problems.

Method used

Cerium oxide is used as the outermost high-durability layer, combined with silicon dioxide as the low-refractive-index surface layer. An optical laminate is formed within a specific thickness range by sputtering to ensure optical properties and durability.

Benefits of technology

It enables the formation of a durable, low-reflectivity, and easy-to-manufacture anti-reflective film on a lightweight resin substrate, which can prevent peeling and damage under harsh conditions such as pen swiping, and is suitable for displays of mobile devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117980786B_ABST
    Figure CN117980786B_ABST
Patent Text Reader

Abstract

An optical laminate is formed by stacking at least two visible light transmissive optical functional layers, characterized in that the optical functional layers include a first functional layer and a second functional layer, the first functional layer at least contains cerium oxide, has a refractive index at a wavelength of 550 nm ranging from 1.8 to 2.6, and a film thickness ranging from 60 nm to 130 nm, and the second functional layer is formed to ground with the upper surface of the first functional layer, has a refractive index at a wavelength of 550 nm ranging from 1.4 to 1.6, and a film thickness ranging from 80 nm to 100 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an optical laminate with improved durability and an anti-reflective film using the optical laminate.

[0002] This application claims priority based on Japanese Patent Application No. 2021-162974 filed on October 1, 2021, the contents of which are incorporated herein by reference. Background Technology

[0003] Previously, optical multilayer films (optical laminates), which consist of multiple transparent materials of similar thickness to the wavelength of light, have been applied in various fields. For example, anti-reflective films that reduce surface reflection by staggering the phase of reflection, and wavelength-selective films that allow only specific wavelengths to be transmitted or reflected, have been used in camera lenses and window glass. In addition, the visibility of displays such as televisions is sometimes reduced due to the reflection of external light; by applying anti-reflective films, visibility can be improved.

[0004] On the other hand, with the advancements in electronic technology in recent years leading to miniaturization and lightweight designs, displays are increasingly being incorporated into portable devices, such as laptops and smartphones, which feature high-resolution displays. Furthermore, with the increasing IT integration in automobiles, multiple displays showing various information are now integrated into instruments such as speedometers and navigation systems.

[0005] For applications of such optical multilayer films, from a portability perspective, lightweight construction is desired, requiring the formation of anti-reflective films on lightweight films such as resin, rather than on the heavy glass used in the past. Furthermore, even when the display is made of glass, it is preferable to pre-apply the film to the surface to prevent scattering in the event of breakage; anti-reflective films are often applied to prevent such scattering as well.

[0006] As methods for forming optical multilayer films, wet deposition methods, which involve coating materials with different refractive indices in the atmosphere, and dry deposition methods, which involve depositing film-forming materials in a vacuum through sputtering or other means, are generally known. Wet deposition methods are simple, but the materials that can be coated are limited, making it difficult to form optical functional layers with the optical properties required for high-performance optical multilayer films. In addition, it is difficult to form laminates with multiple optical functional layers.

[0007] In contrast, dry deposition methods can easily form multilayer films by stacking multiple materials multiple times. There are several methods of dry deposition, especially the plasma sputtering method using vacuum, which can easily form films even with high melting point target materials and has the advantages of easily ensuring uniform film thickness. It is widely used in the deposition of optical multilayer films.

[0008] In addition, especially when using sputtering, film can be formed with a uniform film thickness distribution over a long period of time. Therefore, the roller-to-roll sputtering device, which combines a sputtering film forming device with a film conveying device, can form a large area of ​​film in one go, which has industrial advantages.

[0009] However, in optical multilayer films, especially with the expanding applications of antireflective films, damage to these films has become a problem. Antireflective films are composed of thin films ranging from a few nm to hundreds of nm in thickness. Even a partial peeling or detachment disrupts optical interference conditions, significantly altering the optical properties of the detached portion. Therefore, it is challenging to easily visually identify such defects. For example, in laptops and smartphones, touchscreen modules are integrated into the touch panel. Repeated sliding of the antireflective film with a sharp stylus or similar device concentrates the load locally on the antireflective film. This increasing frequency of use necessitates improving the rigidity (mechanical strength) of the antireflective film itself.

[0010] For example, Patent Document 1 discloses that in order to improve the durability of the transparent conductive film for pen input, the temperature of the film substrate is increased during film formation, or impurities such as moisture and organic matter in the film formation atmosphere are removed to make the surface hardness of the film 0.4 to 0.8 GPa, thereby maintaining the durability of the transparent conductive film.

[0011] In addition, Patent Document 2 discloses that by using ECR (Electron Cyclone Resonance) plasma, the water absorption rate of the transparent plastic material is reduced to less than 0.02%, and the Vickers hardness of the film is increased to 15 or higher, thereby improving the scratch resistance of the film.

[0012] In addition, Patent Document 3 discloses a method for forming a high refractive index layer by using tantalum pentoxide through ion-assisted vapor deposition, thereby achieving a compressive stress of 150-250 MPa, which improves heat resistance and hardness.

[0013] Furthermore, Patent Document 4 discloses a multilayer film containing a diamond layer, which has diamond crystals or is composed of diamond crystals, and uses alumina, crystalline alumina, or a mixture of Al2O3 and SiO2 as a covering layer covering the top of it, thereby forming a film with high hardness and giving it scratch resistance.

[0014] Existing technical documents

[0015] Patent documents

[0016] Patent Document 1: Japanese Patent Application Publication No. 2002-163932

[0017] Patent Document 2: Japanese Patent Application Publication No. 2005-066937

[0018] Patent Document 3: Japanese Patent Application Publication No. 2009-217018

[0019] Patent Document 4: Japanese Patent No. 6713485 Summary of the Invention

[0020] The problem that the invention aims to solve

[0021] However, Patent Document 1 is a technology that can only be applied to conductive oxides with a limited composition, such as composite oxides of indium oxide and tin oxide, and is not suitable for antireflective films that do not require conductivity.

[0022] In addition, Patent Document 2 has difficulty in stably forming ECR plasma for a long time, especially in terms of productivity for stable production of continuous roll-to-roll sputtering on the film.

[0023] Furthermore, in Patent Document 3, since ion-assisted evaporation is used, it is difficult to apply to the formation of antireflective films by sputtering.

[0024] Furthermore, in Patent Document 4, since the filament generates high temperatures of 800–2500°C, the substrate is required to have high heat resistance, making it impossible to use a resin substrate with low heat resistance. In addition, the capping layer is formed by magnetron sputtering, which results in large differences in film formation speed and process vacuum levels. Therefore, the equipment becomes larger and more complex in the simultaneous and continuous film formation process, making mass production difficult.

[0025] On the other hand, when antireflective films are made of dielectric multilayer films, the outermost layer mostly uses low refractive index materials with a refractive index of about 1.5, especially silicon oxide and composite oxides with silicon oxide as the main component. However, peeling may occur in repeated sliding based on pen input, etc.

[0026] Furthermore, while so-called hard materials such as zirconium oxide are harder than silicon oxide, their refractive index is as high as around 2.0, making them difficult to apply to the surface of antireflective films. In addition, aluminum oxide is an example of a relatively low-refractive-index (around 1.7) and hard material, but its sputtering deposition rate is very low, the deposition process is complex, and its optical properties are lower than those of silicon oxide.

[0027] Therefore, it is desirable to have an optical laminate that does not peel even under harsh conditions such as pen gliding, can achieve sufficient anti-reflective properties, and is easy to manufacture.

[0028] The present invention was made with regard to the following circumstances, and its object is to provide an optical laminate that is highly durable against physical stress, has a low refractive index and is easy to manufacture, and an antireflective film using the same.

[0029] Methods for solving problems

[0030] To address the aforementioned issues, the inventors have discovered that by using a low-refractive-index material such as silicon oxide to form the outermost optical functional film to a specific thickness, and by using a high-hardness material to form the underlying optical functional film to a specific thickness, it is possible to obtain an optical laminate that exhibits high durability against physical stress, low reflectivity, and ease of manufacturing.

[0031] In other words, in order to solve the above-mentioned problems, the present invention proposes the following solution.

[0032] The optical laminate of the present invention is characterized in that it is an optical laminate formed by stacking at least two visible light transmissive optical functional layers, wherein the optical functional layers include a first functional layer and a second functional layer; the first functional layer contains at least cerium oxide, has a refractive index of 1.8 or more and 2.6 or less at a wavelength of 550 nm, and a film thickness of 60 nm or more and 130 nm or less; the second functional layer is formed in contact with the upper surface of the first functional layer, has a refractive index of 1.4 or more and 1.6 or less at a wavelength of 550 nm, and a film thickness of 80 nm or more and 100 nm or less.

[0033] According to the present invention, by forming a first functional layer made of a material containing cerium oxide in a thickness range of 60 nm to 130 nm in a manner that is in contact with the lower surface of the second functional layer which is the outermost layer of the optical laminate, sufficient optical properties as an optical laminate, such as an anti-reflective film, can be obtained, and even if strong physical stress, such as that causing a pen to slide on the surface, is applied, the function can be improved by the durability of the first functional layer, and sufficient durability such as protection against damage can be obtained.

[0034] In addition, in this invention, the second functional layer can also constitute the uppermost layer of the optical laminate.

[0035] Furthermore, in this invention, the first functional layer may contain at least one metal oxide other than cerium oxide in an elemental ratio of 0.1% to 50%.

[0036] In addition, in this invention, the second functional layer may contain at least silicon.

[0037] The antireflective film of the present invention is characterized by the use of the optical laminate described in the foregoing.

[0038] In addition, in this invention, the aforementioned optical laminate can be supported on a transparent substrate made of a visible light transmissive polymer film.

[0039] In addition, in this invention, an adhesive layer may be formed between the optical laminate and the transparent substrate.

[0040] Invention Effects

[0041] According to the present invention, it is possible to provide an optical laminate that has high durability against physical stress, low reflectivity and is easy to manufacture, as well as an antireflective film using the same. Attached Figure Description

[0042] [ Figure 1 [Illustration 1] is a cross-sectional view showing an antireflective film of an optical laminate having one embodiment of the present invention. Detailed Implementation

[0043] Hereinafter, an optical laminate according to one embodiment of the present invention and an antireflective film using the same will be described with reference to the accompanying drawings. Furthermore, the embodiments shown below are specifically described to better understand the gist of the invention, and are not intended to limit the invention unless otherwise specified. Additionally, in the accompanying drawings used in the following description, for ease of understanding of the features of the invention, some parts that will be considered major components are sometimes shown enlarged, and the dimensional ratios of the constituent elements may not be the same as actual dimensions.

[0044] An example of an antireflective film using an optical laminate according to one embodiment of the present invention will be provided for illustration.

[0045] Additionally, the following explanation mentions that transparency means the ability to transmit light in the visible light wavelength range (approximately 360 nm to 830 nm).

[0046] Figure 1 This is a cross-sectional view showing an antireflective film having an optical laminate according to one embodiment of the present invention. The antireflective film 10 of this embodiment has a transparent substrate 11, an optical laminate 12 formed overlapping one side of the transparent substrate 11, an adhesive layer 13 formed between the transparent substrate 11 and the optical laminate 12, and an antifouling layer 14 formed overlapping the upper surface of the optical laminate 12.

[0047] In addition, the optical laminate 12 has a high-durability layer (first functional layer) 21, a low-refractive-index surface layer (second functional layer) 22 formed in contact with the upper surface of the high-durability layer 21, and an optical functional multilayer film 23 formed in contact with the lower surface of the high-durability layer 21.

[0048] The transparent substrate 11 can be formed of a transparent material capable of transmitting light in the visible light wavelength range; for example, a polymer film with a visible light transmittance of 88% or more is preferably used. Specific examples of the constituent materials of the polymer film include polyester resins, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins.

[0049] More specifically, examples include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyarylamide, polyimide, polycarbonate, polyethylene, polypropylene, triacetyl cellulose (TAC), and polycyclic olefins (COC, COP).

[0050] The thickness of the transparent substrate 11 is not particularly limited, but is preferably in the range of 20 μm or more and 1000 μm or less. If the thickness of the transparent substrate 11 is 20 μm or more, the rigidity of the substrate itself is ensured, and wrinkles are not easily generated even when stress is applied to the antireflective film 10.

[0051] When manufacturing the antireflective film 10 using a roll-to-roll method, if the thickness of the transparent substrate 11 is 1000 μm or less, it is easy to roll the antireflective film 10 during manufacturing and the manufactured antireflective film 10 into a roll shape, enabling efficient manufacturing of the antireflective film 10. Furthermore, if the thickness of the transparent substrate 11 is 1000 μm or less, it is possible to achieve thinner and lighter antireflective film 10. If the thickness of the transparent substrate 11 is 600 μm or less, it is preferable to manufacture the antireflective film 10 more efficiently and further achieve thinner and lighter weight.

[0052] The transparent substrate 11 may contain reinforcing materials, such as cellulose nanofibers or nano-silica, provided that the optical properties are not significantly impaired. Polyester-based resins, acetate-based resins, polycarbonate-based resins, and polyolefin-based resins are particularly preferred. Specifically, triacetyl cellulose (TAC) substrate is preferred.

[0053] It should be noted that the transparent substrate 11 can also be a film endowed with optical or physical functions. Examples of substrates with optical or physical functions include polarizers, phase difference compensation films, thermal ray interception films, transparent conductive films, brightness enhancement films, and barrier properties enhancement films.

[0054] Optical laminate 12 is a layer that represents optical functions. The optical functions referred to here are the functions that control the reflection, transmission, and refraction of light, such as anti-reflection functions, selective reflection functions, anti-glare functions, and lens functions.

[0055] The optical laminate 12 can be any layer that functions as an anti-reflective layer, a selective reflection layer, or an anti-glare layer. In this embodiment, the optical laminate 12 is a layer that performs the anti-reflective function.

[0056] The high-durability layer (first functional layer) 21 constituting the optical laminate 12 is a layer that improves the durability against physical stresses applied to the surface of the optical laminate 12.

[0057] The high-durability layer 21 is composed of a material containing at least cerium oxide. In this embodiment, the high-durability layer 21 is formed of cerium dioxide (CeO2). It should be noted that the high-durability layer 21 may also be formed by replacing Ce in the cerium dioxide with Nb in an elemental ratio of 0.1% or more and 50% or less. In this case, the film formation rate and the stability of the discharge can be improved in the sputtering-based film formation process described later.

[0058] The high-durability layer 21 is formed with a film thickness ranging from 60 nm to 130 nm. If the film thickness is less than 60 nm, sufficient durability may not be achieved. In addition, if the film thickness exceeds 130 nm, there is a concern about a reduction in optical properties.

[0059] The refractive index of this high-durability layer 21 at a wavelength of 550 nm is in the range of 1.8 or higher and 2.6 or lower. By setting it to such a range of refractive index, the optical functions of the optical laminate 12, such as anti-reflective function, can be appropriately maintained.

[0060] The low-refractive-index surface layer (second functional layer) 22 constituting the optical laminate 12 is formed in direct contact with the upper surface of the high-durability layer 21. Such a low-refractive-index surface layer 22 can be made of silicon dioxide (SiO2). A single-layer SiO2 film is colorless and transparent. For example, the low-refractive-index surface layer 22 only needs to contain more than 50% by mass of SiO2.

[0061] It should be noted that, in addition to SiO2, the low refractive index surface layer 22 preferably contains Na for the purpose of improving durability, Zr, Al or N for the purpose of improving hardness, and Zr or Al for the purpose of improving alkali resistance.

[0062] The refractive index of the low refractive index surface layer 22 is in the range of 1.4 to 1.6, preferably in the range of 1.4 to 1.5.

[0063] In addition, the thickness of the low refractive index surface layer 22 can be in the range of 80nm to 100nm, and can be appropriately selected according to the wavelength range required for anti-reflection function.

[0064] The optical functional multilayer film 23 constituting the optical laminate 12 is a laminate in which a high refractive index layer 23a and a low refractive index layer 23b are sequentially stacked from the transparent substrate 11 side. In addition, the number of high refractive index layer 23a and low refractive index layer 23b can be two or more, or any number of layers, as in this embodiment.

[0065] As in this embodiment, by constructing an optically functional multilayer film 23 from a laminate of a low-refractive-index layer 23b and a high-refractive-index layer 23a, a portion of light incident from the low-refractive-index surface layer 22 side, such as external light, is reflected within the optically functional multilayer film 23, the high-durability layer 21, and the low-refractive-index surface layer 22, interfering at the surface in a manner that cancels out each other's phases, thereby substantially suppressing reflection. Therefore, an anti-reflection function that prevents external light incident from the low-refractive-index surface layer 22 side can be obtained.

[0066] The optically functional multilayer film 23 is composed of a material containing inorganic oxides or inorganic nitrides. From the viewpoint of ease of acquisition and cost, the low refractive index layer 23b can be made of silicon dioxide (SiO2). A SiO2 monolayer film is colorless and transparent. For example, the low refractive index layer 23b only needs to contain more than 50% by mass of SiO2.

[0067] In addition to SiO2, the low refractive index layer 23b preferably contains Na for improving durability, Zr, Al or N for improving hardness, and Zr or Al for improving alkali resistance.

[0068] The refractive index of the low refractive index layer 23b is preferably 1.20 to 1.60, more preferably 1.30 to 1.50.

[0069] In addition, the thickness of the low refractive index layer 23b only needs to be in the range of 1 nm or more and 200 nm or less, and can be appropriately selected according to the wavelength region required for the anti-reflection function. However, in this embodiment, by setting it to 10 nm to 40 nm, when the high durability layer (first functional layer) 21 and the low refractive index surface layer (second functional layer) 22 are set to a specified thickness, the optical properties such as reflectivity and transmittance become good, which is more preferred.

[0070] For example, niobium pentoxide (Nb₂O₅, refractive index 2.33), titanium oxide (TiO₂, refractive index 2.33–2.55), tungsten oxide (WO₃, refractive index 2.2), cerium oxide (CeO₂, refractive index 2.2), tantalum pentoxide (Ta₂O₅, refractive index 2.16), zinc oxide (ZnO, refractive index 2.1), indium tin oxide (ITO, refractive index 2.06), and zirconium oxide (ZrO₂, refractive index 2.2) can be used as the high refractive index layer 23a. Furthermore, if it is desired to impart conductive properties to the high refractive index layer 23a, ITO or indium zinc oxide (IZO) can also be used.

[0071] In addition, the thickness of the high refractive index layer 23a can be, for example, 1 nm or more and 200 nm or less, and can be appropriately selected according to the wavelength region required for the anti-reflection function. However, in this embodiment, by setting it to 10 nm to 40 nm, when the high durability layer (first functional layer) 21 and the low refractive index surface layer (second functional layer) 22 are set to a specified thickness, the optical properties such as reflectivity and transmittance become good, which is more preferred.

[0072] In this embodiment, the optical functional multilayer film 23 is a high refractive index layer 23a made of niobium pentoxide (Nb2O5, refractive index 2.33) and a low refractive index layer 23b made of silicon dioxide (SiO2).

[0073] The adhesive layer 13 is formed to improve the adhesion between the transparent substrate 11 and the optical laminate 12. The adhesive layer 13 is preferably composed of an oxygen-deficient metal oxide or a metal. An oxygen-deficient metal oxide refers to a metal oxide with an insufficient number of oxygen atoms compared to its stoichiometric composition. Examples of oxygen-deficient metal oxides include SiOx, AlOx, TiOx, ZrOx, CeOx, MgOx, ZnOx, TaOx, SbOx, SnOx, and MnOx. Examples of metals include Si, Al, Ti, Zr, Ce, Mg, Zn, Ta, Sb, Sn, Mn, and In. The adhesive layer can be, for example, an adhesive layer in SiOx where x is greater than 0 and less than 2.0.

[0074] From the viewpoint of maintaining transparency and obtaining good optical properties, the thickness of the sealing layer is preferably greater than 0.1 nm and less than 20 nm, and particularly preferably greater than 1 nm and less than 10 nm.

[0075] The antifouling layer 14 is a layer used to prevent contamination of the optical laminate 12. For example, it can be a coating layer of an alkoxysilane compound having a perfluoropolyether group. By covering the surface of the optical laminate 12 with an alkoxysilane compound having a perfluoropolyether group, the water contact angle of the surface of the optical laminate 12 exhibits a water repellency of, for example, greater than 110 degrees, thereby improving antifouling properties.

[0076] It should be noted that although the optical laminate 12 of this embodiment has an optically functional multilayer film 23, the optical laminate of the present invention can be formed by at least two layers: a high-durability layer (first functional layer) 21 and a low-refractive-index surface layer (second functional layer) 22 formed in contact with the upper surface of the high-durability layer 21. Furthermore, although the antireflective film 10 of this embodiment is provided with an adhesive layer 13 and an antifouling layer 14, it can also be configured without either or both of these adhesive layers 13 and antifouling layers 14.

[0077] Alternatively, a layer with functions such as selective reflection, anti-glare, polarization, phase difference compensation, viewing angle compensation or magnification, light guiding, diffusion, brightness enhancement, hue adjustment, and conductivity can be further formed on the other side of the transparent substrate 11.

[0078] In addition to a smooth shape, the surface shape of the optical laminate 12 can also be a nanoscale uneven structure with features such as revealing moth eyes and anti-glare. Alternatively, it can be a geometric shape ranging from micrometers to millimeters, such as a lens or prism. The shape can be formed, for example, through a combination of photolithography and etching, shape transfer, hot pressing, etc. In this embodiment, since the film is formed by vacuum deposition, the uneven shape can be maintained even if it exists on the substrate.

[0079] According to the optical laminate 12 of this embodiment with the structure described above, and the antireflective film 10 having the optical laminate 12, a high-durability layer (first functional layer) 21 made of a cerium oxide-containing material is formed in contact with the lower surface of the low-refractive-index surface layer (second functional layer) 22, which is the outermost layer of the optical laminate 12. This allows for sufficient optical properties as an optical functional film, such as an antireflective film, and even when subjected to strong physical stress such as sliding a pen on the surface, sufficient durability, such as preventing damage, can be obtained through the function of the high-durability layer (first functional layer) 21. If such an antireflective film 10 is applied to the display unit of a pen-based mobile device or a notebook computer, the lifespan of the display unit can be extended.

[0080] Next, one embodiment of the method for manufacturing an antireflective film having the optical laminate described above will be described.

[0081] As an example of the manufacturing method of the antireflective film in this embodiment, the antireflective film 10 can be manufactured by using a transparent substrate 11 wound into a roll shape to manufacture the antireflective film 10 and then wound into a roll shape in a so-called roll-to-roll manner.

[0082] First, a transparent substrate (substrate) 11 wound into a roll shape is unwound. Then, an optical laminate 12 is formed on one side of the transparent substrate 11. The optical laminate 12 can be formed, for example, by using a sputtering device, applying a voltage to a target containing materials constituting each layer, and supplying a specified reactive gas and argon gas to generate plasma at a specified flow rate.

[0083] For example, when forming the high-durability layer (first functional layer) 21, CeO2 is used as the target material, argon is used as the plasma generating gas, and O2 is used as the reactive gas. Alternatively, for example, when forming a layer composed of SiO2 as a low-refractive-index surface layer (second functional layer) 22, Si is used as the target material, argon is used as the plasma generating gas, and O2 is used as the reactive gas.

[0084] In this way, by sputtering each layer onto one side of the transparent substrate 11, an antireflective film with an optical laminate can be easily manufactured.

[0085] The embodiments of the present invention have been described above, but these embodiments are provided as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their variations are included in the scope and spirit of the invention, and are also included in the scope of the invention as described in the claims and its equivalents.

[0086] Example

[0087] (Verification Example 1)

[0088] First, the hardness of the cerium oxide film used as the high-durability layer (first functional layer) 21 was measured.

[0089] Thin films of cerium dioxide (CeO2) as Example 1 of the present invention, silicon dioxide (SiO2) as Comparative Example 1, niobium pentoxide (Nb2O5) as Comparative Example 2, and zirconium dioxide (ZrO2) as Comparative Example 3 were formed on a glass substrate.

[0090] RF sputtering apparatus was used for film deposition in each thin film. The exhaust system of the RF sputtering apparatus used in film deposition consisted of a turbomolecular pump and a rotary pump, capable of exhausting to 5 × 10⁻⁶ ppm. -4 Below Pa. Four cathodes are arranged within the vacuum chamber (film formation chamber), each capable of holding a target material with a diameter of 2 inches. A gate mechanism is installed between each cathode, allowing the opening and closing times to be controlled by a timer. Therefore, if the film formation rate is known in advance, the film thickness can be precisely controlled by adjusting the gate opening time.

[0091] A gas supply pipeline is connected to the vacuum chamber, capable of supplying reactant gases such as argon, oxygen, and nitrogen, as well as carrier gases. The flow rate of each gas can be precisely controlled by a mass flow meter located between the gas storage cylinder and the vacuum chamber. A conduction valve is installed between the turbomolecular pump and the vacuum chamber, allowing adjustment of the film-forming pressure to any desired level by adjusting the exhaust speed. The substrate can be placed on a stage opposite the target. The stage can rotate to ensure uniform film thickness and can be heated to 300°C. Furthermore, the distance between the stage and the target can also be adjusted.

[0092] In evaluating the hardness of each film, alkali-free glass (OA-10G: manufactured by Nippon Electric Glass Co., Ltd.) was used as the substrate to avoid the influence of the substrate. After washing the substrate with water using a neutral detergent, it was ultrasonically cleaned in an ethanol solution for 10 minutes. After being lifted out of the ethanol solution, the substrate was immediately sprayed with air to remove droplets, so as not to produce dry spots.

[0093] Then, after placing the substrate on the stage within the RF sputtering apparatus with the above-described structure, venting is performed until a pressure of 5 × 10⁻⁶ is reached. -4 Argon and oxygen were introduced at a pressure below Pa. The ratio of argon to oxygen was determined by investigating and determining the conditions under which absorption in the visible light region would not occur. Under these conditions, the films of Examples 1 and Comparative Examples 1 to 3 were formed to a thickness of 400 nm.

[0094] The hardness was measured using a martensitic hardness tester. Table 1 shows the martensitic hardness measurement results of the films of Example 1 and Comparative Examples 1 to 3 respectively. Additionally, as a reference example, the hardness of the glass substrate was also measured.

[0095] [Table 1]

[0096]

[0097] Based on the results of Verification Example 1 shown in Table 1, it can be confirmed that the cerium dioxide film of Example 1, which is used as the high-durability layer (first functional layer) 21, has higher hardness compared to the films of Comparative Examples 1 to 3. Therefore, by using such cerium dioxide to form the high-durability layer (first functional layer) 21, the surface durability of the optical laminate 12 can be improved.

[0098] (Verification Example 2)

[0099] Samples of Examples 10 to 16 and Comparative Examples 10 to 16 as shown below were prepared, and the reflectivity and durability (steel wool test) of each sample were measured.

[0100] [Example 10]

[0101] A substrate with an acrylic resin layer formed on one side of a triacetyl cellulose (TAC) film was used. The substrate was placed in an RF sputtering apparatus, and after venting the chamber, film deposition was performed. Niobium pentoxide (a high-refractive-index layer in the optical functional film) and silica (a low-refractive-index layer in the optical functional film) were sequentially deposited. Then, cerium dioxide (a high-durability layer, the first functional layer) was deposited to a thickness of 100 nm. Finally, a 90 nm layer of silica (a low-refractive-index surface layer, the second functional layer) was stacked on top, and the sample was removed from the chamber. For the removed sample, an alkoxysilane compound with perfluoropolyether groups was used as an antifouling layer. This was applied by spin coating to a thickness of 3 nm to 5 nm, and the sample was allowed to stand at room temperature for one day to obtain the sample of Example 1.

[0102] [Example 11]

[0103] The thickness of cerium dioxide was set to 60 nm, and the sample was prepared under the same conditions as in Example 1.

[0104] [Example 12]

[0105] The thickness of cerium dioxide was set to 130 nm, and the sample was prepared under the same conditions as in Example 1.

[0106] [Example 13]

[0107] The thickness of silicon dioxide on cerium dioxide was set to 80 nm, and the sample was prepared under the same conditions as in Example 1.

[0108] [Example 14]

[0109] The sample was prepared under the same conditions as in Example 1, except that the thickness of the cerium dioxide was 120 nm and the thickness of the silicon oxide on the cerium oxide was 100 nm.

[0110] [Example 15]

[0111] Nb is used by replacing a portion of the Ce in cerium dioxide with Nb. 0.2 Ce 0.8 O was used instead of cerium dioxide, and the samples were prepared under the same conditions as in Example 1.

[0112] [Example 16]

[0113] Nb is used by replacing a portion of the Ce in cerium dioxide with Nb. 0.4 Ce 0.6 O was used instead of cerium dioxide, and the samples were prepared under the same conditions as in Example 1.

[0114] [Comparative Example 10]

[0115] Niobium pentoxide was used instead of cerium dioxide, and its thickness was set to 110 nm. Otherwise, the sample was prepared under the same conditions as in Example 1.

[0116] [Comparative Example 11]

[0117] The thickness of cerium dioxide was set to 110 nm, and no silicon oxide was formed on it. Otherwise, the sample was prepared under the same conditions as in Example 1.

[0118] [Comparative Example 12]

[0119] The thickness of cerium dioxide was set to 50 nm, and the sample was prepared under the same conditions as in Example 1.

[0120] [Comparative Example 13]

[0121] The thickness of cerium dioxide was set to 140 nm, and the sample was prepared under the same conditions as in Example 1.

[0122] [Comparative Example 14]

[0123] The thickness of silicon oxide on cerium dioxide was set to 70 nm, and the sample was prepared under the same conditions as in Example 1.

[0124] [Comparative Example 15]

[0125] The thickness of cerium dioxide was set to 120 nm, and the thickness of silicon oxide on it was set to 110 nm. Otherwise, the sample was prepared under the same conditions as in Example 1.

[0126] <Measurement of Reflectivity>

[0127] Reflectance was measured using a UH 4150 UV-Vis-NIR spectrophotometer (manufactured by Hitachi High Technology Co., Ltd.). To eliminate the influence of back reflection, the back of each sample was coated with black, and only the surface reflectance was measured. The incident light angle was set to 5°, and measurements were taken in the wavelength range of 300 nm to 800 nm under a positive reflection configuration. Based on the obtained measurement data, the light source was set to D65, the viewing angle was set to 2°, and the stimulus value Y calculated using the calculation method specified in "JIISZ-8701" was defined as the reflectance. As an antireflective film, 0.5% or less is preferred.

[0128] <Steel wool test>

[0129] Cover the clamps (10mm×10mm) of the sliding device with steel wool #0000, apply a load of 1kg, slide the device 100 times on the surface of each sample with a sliding distance of 50mm, remove it from the sliding device, and visually confirm whether any damage has occurred.

[0130] The results of such verification example 2 are shown in Table 2.

[0131] [Table 2]

[0132]

[0133] The evaluation of the results shown in Table 2 is as follows.

[0134] [Results of Examples 10-12]

[0135] As shown in Table 2, if cerium dioxide is deposited in a thickness range of 60 nm to 130 nm, and the thickness of the outermost silicon oxide layer is set to 90 nm, the reflectivity is below 0.5%, thus fully realizing the function of the anti-reflective film. Furthermore, no damage was found in the steel wool test, fully ensuring its damage resistance (durability).

[0136] [Results of Examples 13 and 14]

[0137] The thickness of the outermost silica layer was varied within the range of 80nm to 100nm, and the corresponding cerium oxide thickness was adjusted in a manner that ensured good optical properties to form a film. As a result, the reflectivity was below 0.5%, and no damage was observed in the steel wool test.

[0138] [Results of Examples 15 and 16]

[0139] To improve film formation speed and discharge stability, no more than 40% niobium was added by elemental proportion to form a hard layer. The optical properties were almost unchanged compared with Examples 1 to 5, but a gradual deterioration in damage prevention performance was observed in the steel wool test, and the baseline was barely zeroed at 40% niobium (Example 16).

[0140] [Compare the results of Example 10]

[0141] In the past, when using niobium pentoxide, which is widely used as a high-refractive-index layer, although the optical properties were sufficient, it produced scratches that could be easily visually confirmed in steel wool tests, indicating insufficient damage prevention performance (durability).

[0142] [Compare the results of Example 11]

[0143] When the outermost surface is cerium dioxide instead of silicon dioxide, the steel wool test shows good results, but the reflectivity is very high. When the thickness of the hard film is greater than 60 nm, it is impossible to design an optical layer with a reflectivity of less than 0.5%.

[0144] [Compare the results of Example 12]

[0145] If the thickness of cerium dioxide is set to 50 nm, scratches of a degree that can be easily visually confirmed will appear in the steel wool test, indicating insufficient damage prevention performance (durability). This can be attributed to the fact that sufficient hardness cannot be achieved when the thickness of cerium dioxide is below 50 nm, and the damage resistance of the optical laminate is also deteriorated.

[0146] [Compare the results of Example 13]

[0147] If the thickness of cerium dioxide is set to 140 nm, sufficient hardness is obtained, and the damage resistance of the optical laminate is also improved. However, on the other hand, the reflectivity exceeds 0.5%, resulting in the inability to fully perform its function as an anti-reflective film. When the thickness of the cerium dioxide film is greater than 140 nm, it is known that even adjusting the silicon dioxide in the range of 80 nm to 100 nm cannot achieve sufficient anti-reflective performance.

[0148] [Compare the results of Examples 14 and 15]

[0149] If the thickness of silicon dioxide is less than 70 nm but more than 110 nm, then even if the cerium dioxide is adjusted within the range of 60 nm or more, it cannot fully perform its function as an anti-reflective film. In addition, if the thickness of the silicon dioxide film is more than 110 nm, the effect of the cerium oxide in the hard layer becomes smaller, and in the steel wool test, scratches of a degree that can be easily confirmed by visual inspection are produced, resulting in insufficient damage prevention performance (durability).

[0150] Explanation of reference numerals in the attached figures

[0151] 10…Antireflective film, 11…Transparent substrate, 12…Optical laminate, 13…Sealing layer, 14…Antifouling layer, 21…High-durability layer (first functional layer), 22…Low-refractive-index surface layer (second functional layer), 23…Optical functional multilayer film, 23a…High-refractive-index layer, 23b…Low-refractive-index layer.

Claims

1. An optical laminate, characterized in that it is An optical laminate consisting of at least two layers of visible light transmittance optical functional layers stacked together. The optical functional layer includes a first functional layer, a second functional layer, a high refractive index layer, and a low refractive index layer. The first functional layer contains at least cerium oxide, has a refractive index of 1.8 or higher and 2.6 or lower at a wavelength of 550 nm, and a film thickness of 60 nm or higher and 130 nm or lower. The second functional layer is formed by grounding the upper surface of the first functional layer and constituting the uppermost layer of the optical laminate. Its refractive index at a wavelength of 550 nm is in the range of 1.4 to 1.6, and its film thickness is in the range of 90 nm to 100 nm. The low-refractive-index layer is formed by grounding the lower surface of the first functional layer. The high refractive index layer is formed by grounding the lower surface of the low refractive index layer, and is any one of niobium pentoxide, titanium oxide, tungsten oxide, tantalum pentoxide, zinc oxide, indium tin oxide, and zirconium oxide.

2. The optical laminate according to claim 1, characterized in that, The first functional layer contains at least one metal oxide other than cerium oxide, in an elemental ratio of 0.1% to 50%.

3. The optical laminate according to claim 1, characterized in that, The second functional layer contains at least silicon.

4. An anti-reflective film, characterized in that, Use the optical laminate as described in claim 1 or 2.

5. The antireflective film according to claim 4, characterized in that, The optical laminate is supported on a transparent substrate made of a visible light transmissive polymer film.

6. The antireflective film according to claim 5, characterized in that, An adhesive layer is formed between the optical laminate and the transparent substrate.

Citation Information

Patent Citations

  • Transparent electrically conductive film, transparent electrically conductive sheet and touch panel

    JP2002163932A

  • Functional plastic member

    JP2005066937A

  • Optical article and method for manufacturing optical article

    JP2009217018A

  • Information processing system, information processing device, server device, program, or method

    JP2021162974A

  • Multilayered antireflection film of optical parts made of synthetic resin

    JP1993053001A